Analisis Tingkat Kesehatan Bank Terhadap Kinerja Bank Dengan Metode RGEC : Studi Pada Bank Syariah Indonesia Periode 2021-2022 - Dinita Mayangsari; Ersi Sisdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the level of bank health and performance of Indonesian sharia banks using the RGEC method during the 2021-2022 period. Through this holistic approach, the research examines aspects of bank health, including risk profile, good corporate governance, income and capital. Data was obtained from the financial report of PT Bank Syariah Indonesia Tbk, and analysis was carried out on credit risk, Good Corporate Governance (GCG), Return on Assets (ROA), and Capital Adequacy Ratio (CAR). Research findings show that Indonesian sharia banks demonstrate health and stability in their operations, despite a decline in several performance indicators. These conclusions provide valuable insights for stakeholders in the Islamic banking industry to improve bank performance and stability.